Flame spray pyrolyzed carbon-encapsulated Au/Fe3O4 nanoaggregates enabled efficient photothermal therapy and magnetic hyperthermia of esophageal cancer cells - Wang, Zida; Liu, Gongzhe; Zhou, Jiangping; Zhao, Xiaogang; Cai, Jie (Frontiers in Bioengineering and Biotechnology, 2024)
Multifunctional magneto-plasmonic nanoparticles with magnetic hyperthermia and photothermal therapy could fulfill highly efficient killing of cancer cells. Herein, carbon encapsulated Au/Fe3O4 (Au/Fe3O4@C) were fabricated using an enclosed flame spray pyrolysis. The nanostructures including Fe3O4 core (51.9-55.2 nm) with an obvious decreasing carbon shell thickness and Au core (4.68-8.75 nm) coated with 2-4 graphite layers were tailored by tuning the C2H4 content in the reacting gas mixture. The saturation magnetization (33.7-48.2 emu/g) and optical absorption were aroused.Carbon shell facilitated the dispersion of Au/Fe3O4 and restrained their laser-induced and magnetic field-induced coalescence and growth. Au/Fe3O4@C exhibited excellent magnetic resonance imaging capability (91.4 mM -1 s -1 ) and photothermal performance (65.4 o C for 0.8 mg/mL Au/Fe3O4@C at the power density of 1.0 W/cm 2 after 300 s near-IR laser irradiation (808 nm)). Moreover, the combined application of photothermal and magnetic-heating properties reduced the required intensity of both laser and magnetic field compared to the intensity of separate situation. Our work provided a unique intriguing approach to prepare multi-component core/shell nanoaggregates as well as a promising candidate for the therapy of esophagus cancer cells.